FAKTOR-FAKTOR RISIKO YANG BERPENGARUH TERHADAP FENOMENA KECURANGAN PELAPORAN KEUANGAN PADA INSTITUSI PERBANKAN DI INDONESIA - Priyandani, Myra Shafira; Handayani, Rr. Sri (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
Banking industry is the most fragile sector toward fraud, and fraudulent financial statements is one of the kind of fraud itself. Although fraudulent financial statements is less likely to occur, but the loss that has been caused is very large, it can even reach 10 times the loss by other kind of frauds. Since banking industry serves as the collector and distributor of customer funds, fraud can be easily happen. Despite there are so many regulations and monitoring toward banking activities from OJK and BI, fraudulent financial statements still happens. There are many contributing factors of the occurrence of fraudulent financial statements, such as opportunity, pressure, capability, and rationalization. In particular, free cash flow, shortage of anti fraud programs, management override, and collusion are the risk factors that possibly caused a fraud in a company. The study has the purpose to examine and analyze the influence of free cash flow, anti fraud programs, management override, and collusion towards the indication of fraudulent financial statements toward listed Banking Companies in Indonesian Stock Exchange in 2017-2020. This study uses a quantitative method and the result of the study are: the higher amount of free cash flow increase the indication of fraudulent financial statements, meanwhile the lesser amount of anti fraud programs and indication of collusion increase the indication of fraudulent financial statements. Nevertheless, management override in not a determinant factor of the occurrence of fraudulent financial statements.